Domestic and international context and requirements for the improvement of legal regulations on innovation in Vietnam - Cao Thi Thu Anh; Nguyen Phuong Tuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Innovation is recognized as a key driver for economic growth and sustainable development in many countries and Vietnam. However, the current legal system still has many inadequacies and has not kept up with international practices and practices. This paper assesses the current situation, point out legal gaps and propose solutions to improve the legal framework on innovation in Vietnam. The results of the study show that the improvement of innovation law in Vietnam requires a comprehensive, synchronous, flexible, business-centric approach and integration with international standards. The policy recommendations focus on amending specialized laws, improving financial mechanisms, developing high-quality human resources and renewing state management of innovation in order to create a favorable legal environment, strongly promote innovation activities, improve national competitiveness and meet the requirements of international economic integration. Code: 25060504